2009
DOI: 10.1039/b900879a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced H2 adsorption enthalpy in the low-surface area, partially fluorinated coordination polymer Zn5(triazole)6(tetrafluoroterephthalate)2(H2O)2·4H2O

Abstract: A porous coordination polymer containing zinc, 1,2,4-triazolate, and tetrafluoroterephthalate displays a high physisorptive hydrogen adsorption enthalpy of 8 kJ/mol, as a result of fluorine atoms exposed to the pore surface and the structure's small pore size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 32 publications
(3 reference statements)
0
64
0
Order By: Relevance
“…48 The polar C-F bond may be useful for a preferable gas adsorption site. Cheetham and colleagues 9 Fluorine-functionalized MOFs/PCPs S Noro and T Nakamura (Figure 3a). This MOF had a small pore and fluorine atoms exposed on the pore surface (Figure 4a), which was expected to cause high enthalpy of H 2 adsorption (-8 kJ mol − 1 at low coverage, Figure 4b), comparable to MOFs with coordinatively unsaturated metal centers that considerably increase this value.…”
Section: Mofs Containing Fluorine-and Trifluoromethyl-substituted Orgmentioning
confidence: 99%
“…48 The polar C-F bond may be useful for a preferable gas adsorption site. Cheetham and colleagues 9 Fluorine-functionalized MOFs/PCPs S Noro and T Nakamura (Figure 3a). This MOF had a small pore and fluorine atoms exposed on the pore surface (Figure 4a), which was expected to cause high enthalpy of H 2 adsorption (-8 kJ mol − 1 at low coverage, Figure 4b), comparable to MOFs with coordinatively unsaturated metal centers that considerably increase this value.…”
Section: Mofs Containing Fluorine-and Trifluoromethyl-substituted Orgmentioning
confidence: 99%
“…Structures containing many types of coordinating organic molecules have been synthesized [6], but the use of perfluorinated molecules or even partially-fluorinated molecules as ligands has been largely ignored to date. Recently, reports by ourselves and Omary have indicated that porous materials containing exposed fluorine atoms display interesting hydrogen storage properties [7][8][9]. There have also been examples of interesting luminescence and catalytic properties in lanthanide materials containing large trifluoromethyl-substituted ligands [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…3a), was found to be porous with a rather modest surface area of 150 m 2 /g. The isosteric heat of adsorption 3 for hydrogen in this material was found to be as high as 8 kJ/mol over a considerable range of loadings, which is more than 50 % higher than that in a typical MOF (without F substitution). This result was convincingly supported by our inelastic neutron scattering data on this system obtained on the TOFTOF Spectrometer of the FRM-II reactor at the Technical University of Munich, Germany ( This line of investigation was logically continued to include the larger bipyridine-based ligands in combination with perfluorinated dicarboxylates in order to achieve significant porosity in these materials, and we were able to synthesize several phases incorporating the ligands 1,2-bis(4-pyridyl)ethane (bpa) and 1,3-bis(4-pyridyl)propane, the most interesting of which is a structure containing zinc 4 , 1,2-bis(4-pyridyl)ethane and tetrafluoroterephthalate (tftpa) (Fig.…”
Section: Summary Of Project Activitiesmentioning
confidence: 69%
“…We were successful in synthesizing a very large number of novel, previously unknown hybrid materials which incorporate fluorinated links. Only one of these compounds 3 (Fig. 3a), was found to be porous with a rather modest surface area of 150 m 2 /g.…”
Section: Summary Of Project Activitiesmentioning
confidence: 99%